Molecular identification of neuraminidase gene mutations in influenza A/H1N1 and A/H3N2 isolates of Mazandaran province, north of Iran - Mehdi Rabie-Rudsari; Emad Behboudi; Ategheh Ranjkesh; Kimia Kaveh; Hadi Razavi-Nikoo; Mohammad Reza Haghshenas; Abdolvahab Moradi (Journal of Global Antimicrobial Resistance, 2024)
Objectives: The neuraminidase (NA) mutations causing resistance to NA inhibitors (NAIs) mostly compromise the fitness of influenza viruses. Considering the importance of these mutations, constant monitoring of the effectiveness of available drugs is critical. This study aimed to identify NA mutations in the influenza A/H1N1 and A/H3N2 subtypes in the samples of Mazandaran, Iran from 2016 to 2020. Methods: In this cross-sectional study, 20 influenza A/H1N1 and 20 influenza A/H3N2 samples were included in the study. After design of appropriate primers for NA gene, all samples subjected to RT-PCR and electrophoresis. Then the PCR product was sequenced to determine the mutations. Results: In the present study, no oseltamivir resistance-related mutations were detected. Still, NA gene showed variations compared to the vaccine strains. In A/H1N1, a total of 43 mutations were detected. Similarly, in A/H3N2, a total of 66 mutations were observed. In all isolates of H1N1, N200S, N248D and I321V mutations were detected in the antigenic site of NA protein, which can affect vaccine incompatibility and virus escape from the host's immune system. Also, H150R mutation was observed in the NA active site of H3N2, which is the cause of agglutination by NA protein. Also, S245N mutation was identified as a new N-Glycosylation site of H3N2 subtype. Conclusions: The study of NA gene sequences revealed no oseltamivir resistance mutations. In H1N1 isolates, ca. 97% identities and in the H3N2 subtype, 96% identities were observed compared to reference isolate of 2009, which indicates the importance of constant monitoring of the emergence of the drug resistance mutations.